2012
DOI: 10.1097/mnm.0b013e328354df7c
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of 227Th-labeled and 177Lu-labeled trastuzumab in mice with HER-2-positive ovarian cancer xenografts

Abstract: The α-particle-emitting RIC (227)Th-trastuzumab effectively delayed tumor growth and prolonged survival of mice compared with β-emitting (177)Lu-trastuzumab administered at the same absorbed radiation dose to tumor. This new therapeutic approach warrants further studies aiming at clinical testing in patients with micrometastatic ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
0
22
1
Order By: Relevance
“…Although herein we do not conduct a comparison with conventional anti-HER2 177 Lu-RIT with an IgG radiolabeled with 177 Lu, it was previously reported by Rasaneh et al 29 with 8- to 10-week-old inbred female BALB/c mice that the calculated mean absorbed doses to tumor and blood during treatment with 7.4 MBq were 6.35 ± 1.2 Gy MBq -1 and 1.62 ± 0.13 Gy MBq -1 , leading to a mean TI for blood of 3.9. During a comparative study of 227 Th-labeled and 177 Lu-labeled trastuzumab in mice bearing HER2(+) SKOV-3 ovarian cancer xenografts, absorbed radiation doses from β-particles emitted from 177 Lu in the tumor and blood were 3.82 ± 0.64 Gy and 1.57 ± 0.64 Gy for 72 MBq/kg 177 Lu-trastuzumab injection, giving an approximate mean TI of 2.4 for blood 30 . In addition, although dosimetry was not described, Ray et al reported that i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Although herein we do not conduct a comparison with conventional anti-HER2 177 Lu-RIT with an IgG radiolabeled with 177 Lu, it was previously reported by Rasaneh et al 29 with 8- to 10-week-old inbred female BALB/c mice that the calculated mean absorbed doses to tumor and blood during treatment with 7.4 MBq were 6.35 ± 1.2 Gy MBq -1 and 1.62 ± 0.13 Gy MBq -1 , leading to a mean TI for blood of 3.9. During a comparative study of 227 Th-labeled and 177 Lu-labeled trastuzumab in mice bearing HER2(+) SKOV-3 ovarian cancer xenografts, absorbed radiation doses from β-particles emitted from 177 Lu in the tumor and blood were 3.82 ± 0.64 Gy and 1.57 ± 0.64 Gy for 72 MBq/kg 177 Lu-trastuzumab injection, giving an approximate mean TI of 2.4 for blood 30 . In addition, although dosimetry was not described, Ray et al reported that i.p.…”
Section: Discussionmentioning
confidence: 99%
“…These specific activities are at least10-fold greater than what has been previously reported for 227 Th-trastuzumab. 39, 5456 Meanwhile, the reported labeling yields for 227 Th-trastuzumab range from 6% to 90%. 55, 56 The percent bound to HER2 was 53.7% for 227 Th-trastuzumab and 26.2% for 227 Th-panitumumab to HER1.…”
Section: Resultsmentioning
confidence: 99%
“…24 This data is consistent with a report by Abbas et al, in which 227 Th-trastuzumab was evaluated in a murine model for ovarian cancer. 54 Others have demonstrated tumor targeting with low uptake in normal organs following i.p. injection of 227 Th-trastuzumab in mice bearing i.p.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Th-trastuzumab turned out to be significantly better than the b --particle-emitting 177 Lu-trastuzumab. 26 The RBE was also studied in mice with breast cancer xenografts, and it was found that it was higher for 227 Th-trastuzumab than for 177 Lutrastuzumab, infact, to achieve 100% prolonged growth delay the absorbed radiation dose of 227 Th-trastuzumab was three times lower than with 177 Lu-trastuzumab. 26 By contrast, the therapeutic index of 177 Lu-trastuzumab was superior to the 227 Th-trastuzumab as when compared with a 50% decrease in the number of white blood cells, the growth delay was three times longer with 177 Lu-trastuzumab than with 227 Thtrastuzumab.…”
mentioning
confidence: 99%